METHODOLOGY FOR ASSESSING THE VALUE OF THE RESIDUAL RISKS IN LANS. ASSESSMENT OF THE RESIDUAL RISK, WHILE ENSURING CONFIDENTIALITY OF INFORMATION OBJECTS - Василенко, В.С.; Дубчак, Е.В.; Василенко, М.Ю (Science-based technologies, 2013)
The technique of estimation of information resources security in the local computer network (LAN) using graphical model is offered in this article. The quality estimation of protection system of confidentiality as one of information functional qualities is defined. Residual risks sizes as quantity indicators of the protection system are defined. The technique provides: the detailed analysis of attacks implementers interaction which are directed on overcoming mechanisms of LAN information security maintenance, with counteraction means these threats that is carried out by information protection service; definition of interaction threats models with counteraction means these threats for protection object – the LAN information resources. Formular expressions for residual risks sizes calculation concerning confidentiality of information objects are resulted and their calculation order is defined on the basis of these models. The technique provides definition of necessary initial data also. Estimations of residual risks sizes, which is received by this technique, allow to define conformity of LAN security level to requirements of information safety policy.